Genetic variations associated with immediate hypersensitivity reactions to iodinated contrast media: A whole exome sequencing study - Noeul Kang; Hoshik Kwon; Myung-Eui Seo; Byung-Joo Min; Byung-Jae Lee; Ju Han Kim; Ho Yun Lee (PLoS ONE, 2026)
Objective The use of iodinated contrast media (ICM) in computed tomography (CT) has increased significantly; however, hypersensitivity reactions (HSRs) remain a concern. This study aimed to investigate genetic factors associated with ICM-induced immediate HSRs using whole exome sequencing (WES). Materials and Methods We conducted a case–control study including 20 patients with ICM-induced immediate HSRs and 11 controls who had received ICM at least three times without HSRs. WES was performed with DNA extracted from saliva samples. Analyses included single-nucleotide variant (SNV) association testing using the Cochran–Armitage trend test with false discovery rate (FDR) correction, gene-wise variant burden (GVB) analysis, and copy number variation (CNV) detection using complementary algorithms. Results A variant in FAST kinase domain 1 ( FASTKD1 , rs12618227) was significantly more prevalent in the control group compared with the case group (72.7% vs. 5.0%, FDR p < 0.10), suggesting a protective role. GVB analysis revealed lower scores for FASTKD1 and 2-hydroxyacyl-CoA lyase 1 ( HACL1 ) in the control group (nominal p < 0.001). CNV analysis identified a significant Signal Regulatory Protein Beta 1 ( SIRPB1 ) deletion in the case group (5/20, 25.0%). In contrast, CNVs in Mucin 12, cell surface associated ( MUC12 ) were observed in both groups. Immune cell expression data showed high expression of FASTKD1 , HACL1 , and SIRPB1 in granulocytes, particularly basophils. Conclusion FASTKD1 and HACL1 , which are involved in mitochondrial and metabolic regulation, and SIRPB1 , which participates in innate immune signaling, were identified as candidate genes potentially associated with ICM-induced immediate HSRs. These suggest a possible contribution of both metabolic and immune regulatory pathways to genetic susceptibility and require validation in larger, independent cohorts before clinical application.